Mountains Piled upon Mountains : Appalachian Nature Writing in the Anthropocene - Cory, Jessica (Book collections on Project MUSE., 2019)
"Mountains Piled upon Mountains features nearly fifty writers from across Appalachia sharing their place-based fiction, literary nonfiction, and poetry. Moving beyond the tradition of transcendental nature writing, much of the work collected here engages current issues facing the region and the planet (such as hydraulic fracturing, water contamination, mountaintop removal, and deforestation), and provides readers with insights on the human-nature relationship in an era of rapid environmental change. This book includes a mix of new and recent creative work by established and emerging authors. The contributors write about experiences from northern Georgia to upstate New York, invite parallels between a watershed in West Virginia and one in North Carolina, and often emphasize connections between Appalachia and more distant locations. In the pages of Mountains Piled upon Mountains are celebration, mourning, confusion, loneliness, admiration, and other emotions and experiences rooted in place but transcending Appalachia's boundaries"--